Discrimination In Women Employment Opportunity: The Case of Tunisia” - Imtinen Ben saied (Communications of International Proceedings, 2023)
Assessing women's access to employment is not a simple task. This requires the use of measurement tools to provide a vision of the level of access to the job market. Although most of these tools are statistical indicators, they do not take into account the characteristics of the woman. In addition, we attempt from this research work to propose a new measurement approach in order to assess the extent of women's access to employment opportunities. Taking into account data from the employment and population survey carried out by the INS in 2017, we construct the female job opportunity index according to the prince of jean Römer's theory of inequality luck. The estimation result of this index shows the inequality distribution in terms of female employment opportunities.
Keywords: employment; opportunity; Tunisia; women; inequality